Serbian migration policy concerning irregular migration and asylum in the context of the EU integration process - Marta Stojić-Mitrović (University of Belgrade, 2016)
In this paper I would like to present Serbian migration policy concerning irregular migration and asylum in the context of the attempts of the Serbian state to become a member of the European Union. I would describe the history of the asylum system prior and after the implementation of the independent asylum system in Serbia in 2008. My presentation of the Serbian migration policy would be channelled by the analysis of some particular political issues, such as the externalization of the EU borders’ control, as well as some relevant elements of the European integration process, like visa liberalization. The second, more culturally specific dimension of the issue would be accessed through the demonstration of both legislative and public conceptualizations of the irregular migrants, asylum seekers and refugees in Serbia.